Bilateral vocal cord palsy as a sole presentation of acquired syphilis - Asha'ari, Zamzil Amin; Razali, Mohd Sayuti; Raja Lope Ahmad, Raja Ahmad Al'konee (Universiti Sains Malaysia, 2010)
Bilateral vocal cord palsy is almost always caused by neck surgery, particularly surgery of the thyroid. We report a case of bilateral vocal cord palsy requiring emergency surgery to relieve the airway obstruction as the sole presentation of acquired syphilis. As the incidence of syphilis worldwide is rising, this unusual presentation may give clinicians a different perspective on the disease.